The Comparison Effect Of Energy Drinks And Coffee On Creatinin Level In Rats - Riza, Mohamad; A, Andina Putri (International Journal of Human and Health Sciences (IJHHS), 2019)
Objective: to compare the effect of administration of energy drinks and coffee on creatinine levels in rats. Methods: an experimental laboratory research using the post test only control group design. The study used 18 male white Sprague Dawley divided into three groups to receive one of the following treatments: 2 cc distilled water,0.072 g /2cc energy drinks and 0.9 g/cc of coffee for 14 days. The creatinine level was evaluated. Data were analyzed by One Way ANOVA test. Results: The mean creatinine level in the aquades group, energy drinks, coffee group was 0.708 mg/dl, 2.05 mg/dl 1.861 mg/dl, respectively. Post Hoc test the LSD test showed a significant difference among these groups (p <0.05). Conclusion: There was a significant different effect between 0.072 g / 2cc energy drinks and 0.9 g/cc coffee on creatinine levels in rat. International Journal of Human and Health Sciences Vol. 03 No. 04 October’19 Page : 231-234